Adsorption of cinnabarinic acid from culture fluid with magnetic microbeads. (6th July 2015) - Göçenoğlu Sarıkaya, Aslı; Osman, Bilgen; Kara, Ali; Pazarlioglu, Nurdan; Beşirli, Necati
Abstract: In this study, antimicrobial pigment cinnabarinic acid (CA) was produced from Pycnoporus cinnabarinus in laboratory‐scale batch cultures. Magnetic poly(ethylene glycol dimethacrylate‐ N ‐methacryloyl‐l‐tryptophan methyl ester) [ m ‐poly(EGDMA‐MATrp)] beads (average diameter = 53–103 µm) were synthesized by copolymerizing of N ‐methacryloyl‐l‐tryptophan methyl ester (MATrp) with ethylene glycol dimethacrylate (EGDMA) in the presence of magnetite (Fe3 O4 ) and used for the adsorption of CA. The m ‐poly(EGDMA‐MATrp) beads were characterized by N2 adsorption/desorption isotherms (Brunauer Emmet Teller), X‐ray photoelecron spectroscopy, scanning electron microscopy, infrared spectroscopy, thermal gravimetric analysis, electron spin resonance and swelling studies. The efficiency of m ‐poly(EGDMA‐MATrp) beads for separation of CA from culture fluid was evaluated. The effects of pH, initial concentration, contact time and temperature on adsorption were analyzed. The maximum CA adsorption capacity of the m ‐poly(EGDMA‐MATrp) beads was 272.9 mg g −1 at pH 7.0, 25 °C. All the isotherm data can be fitted with the Langmuir, Freundlich and Dubinin–Radushkevich isotherm models. The adsorption process obeyed pseudo‐second‐order kinetic model. Thermodynamic parameters Δ H = 5.056 kJ mol −1, Δ S = 52.44 J K −1 mol −1 and Δ G = −9.424 kJ mol− 1 to ‐11.27 kJ mol− 1 with the rise in temperature from 4 to 40 °C indicated that the adsorption process was endothermic and spontaneous. Copyright © 2015 John Wiley & Sons, Ltd.